Corporal Punishment - Scarre, G. (Ethical theory and moral practice, 2003)
This paper examines the reasons why corporal punishment in the judicial sphere has fallen into moral disfavour in recent decades. Standard objections to the practice, both practical and ethical, are considered and found to be inconclusive. It is argued that corporal punishment is not inevitably more cruel or demeaning than conventionally preferred punitive methods and that consideration should be given to its limited experimental reintroduction.